Polarity issues in room temperature ionic liquids - Shukla, Shashi Kant; Kumar, Anil (Clean Technologies and Environmental Policy, 2015)
The study on ionic liquids has occupied an important place in chemical processes because of several beneficial properties. In order to use these ionic liquids as solvent media in chemical processes, it is essential to know their solvent properties. In this review, an attempt has been made to critically evaluate and discuss the polarity parameters of ionic liquids. The experimental polarity data on ionic liquids are not yet available for numerous ionic liquids. This review will serve as a guideline to investigate polarity issues of these materials and emerge with a simple, but still sound theoretical or semi-empirical models to account for the variation in polarity in the ionic liquid solutions.